Quercetin reduces TNF‐α‐induced mesangial cell proliferation and inhibits PTX3 production: Involvement of NF‐κB signaling pathway. (18th July 2019) - Liu, Yue; Yu, Chen; Ji, Kai; Wang, Xuekai; Li, Xin; Xie, Hua; Wang, Yuqing; Huang, Yuting; Qi, Dong; Fan, Huaying
Abstract : Lupus nephritis (LN) is an autoimmune disease caused by systemic lupus erythematosus. Excessive proliferation of mesangial cells is one of the most serious pathological manifestations of LN. In addition, the expression of PTX3 is elevated in the serum of patients with LN. Quercetin has good anti‐inflammatory effects and immunomodulatory activities. In this study, the result of MTT indicated that quercetin treatment alleviated the excessive proliferation of mesangial cells. ELISA and immunofluorescence experiments showed that quercetin treatment inhibited the expression of PTX3. Three doses of quercetin (20, 40, and 80 μM) were selected for the experiment. It is noteworthy that the efficacy of quercetin at 80 μM was significantly better than that of other dose groups. And the effect in inhibiting PTX3 expression was comparable with that of the PDTC (80 μM) positive control. Western blot and qRT‐PCR analysis revealed that quercetin treatment reduced the expression of nuclear factor‐κB p65 and IKKβ, increased the expression of IκBα, and inhibited the expression of PTX3. In conclusion, through inhibiting the activation of nuclear factor‐κB signaling pathway, quercetin treatment could reduce the expression of PTX3 and inhibit the excessive proliferation of mesangial cells, suggesting that quercetin is a potential therapeutic drug for LN.